Real-Time monitoring of sound levels during school sports events - Aigerim Bakatkaliyevna (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: This study examines how impulsive noise impacts athlete performance and spectator behavior at school sports events, using 60 students divided into control and experimental groups to assess effects on reaction time, accuracy, and stress.